(untitled) (Semiárida, 2025)
This study evaluated the effects of prescribed burning as a fire management tool in the shrublands of a protected area in Argentina. The aim was to evaluate the structural, compositional, and functional responses of a Larrea divaricata shrubland during the two years following a prescribed burn, identifying the recovery trajectories and their implications for adaptive management. The prescribed fire was implemented in September 2022 across 408 ha dominated by Larrea divaricata shrublands. Vegetation surveys were carried out before and after the burn (up to 24 months), assessing structure, total and stratified species cover, litter, bare soil, and dead fuel, as well as live/dead shrub density, fine fuel availability, soil seed bank, and soil properties. Three transect belts with fixed sampling stations were established, and statistical analyses included ANOVA, PCA, PerMANOVA, and SIMPER. Significant differences were found only in litter cover and in the 1–2 m vegetation stratum. In all treatments, the highest vegetation cover was consistently concentrated between 20 and 50 cm in height. The dissimilarity in species composition was observed between PreQ and PostQ 24-month treatments. On average, 88 % of shrubs were alive or resprouting following the burn. Two years after the fire, fine fuel load returned to levels close to those observed initially. No significant changes were detected in seedling density or in most soil properties. Maximum temperatures recorded beneath shrubs ranged from 316 to 427 °C, while minimum temperatures in open grassland areas ranged from 121 to 143 °C. This first controlled burn proved effective in reducing fine fuels and promoting vegetation renewal, marking a step forward toward adaptive fire management. Its application in other semi-arid regions will require local ecological characterization, long-term monitoring, and an integrative, evidence-based institutional approach.